Association of Anthropometric Indices with Albumin to Creatinine Ratio and Glomerular Filtration Rate, as Indices of CKD: A Population-based Study (Iranian Journal of Kidney Diseases, 2024)
Introduction. This study was an attempt to detect the relationship between chronic kidney disease (CKD) and anthropometric indices in presence of confounding variables. Methods. A cross-sectional study of 3375 participants was designed in Isfahan city. Waist-height ratio (WHtR), waist-hip ratio (WHR), body mass index (BMI) and waist circumference (WC) were measured. Participants were divided into CKD and non-CKD groups according to the calculated albumin to creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR). Then, the groups were subdivided into sub-groups of high and normal anthropometric indices. Results. To evaluate CKD in relation to anthropometric indices, odds ratio was calculated; in the female group, no association was observed (P ˃ .05). However, in the male group high levels of WHtR and BMI were associated with CKD (P value of .002 and .015, respectively). To evaluate the association between ACR and eGFR with anthropometric indices linear regression analysis was performed. There was no significant relation between ACR and eGFR with anthropometric indices in both sexes in a fully adjusted state (P ˃ .05). Conclusion. High WHtR and BMI probably are associated with CKD in male. WHR and WC have no relation to the occurrence of CKD. There are no significant changes in regard to ACR and eGFR.  DOI: 10.52547/ijkd.7685